A meta‐analysis on growth, physiological, and biochemical responses of woody species to ground‐level ozone highlights the role of plant functional types. (30th August 2017) - Li, Pin; Feng, Zhaozhong; Catalayud, Vicent; Yuan, Xiangyang; Xu, Yansen; Paoletti, Elena
Abstract: The carbon‐sink strength of temperate and boreal forests at midlatitudes of the northern hemisphere is decreased by ozone pollution, but knowledge on subtropical evergreen broadleaved forests is missing. Taking the dataset from Chinese studies covering temperate and subtropical regions, effects of elevated ozone concentration ([O3 ]) on growth, biomass, and functional leaf traits of different types of woody plants were quantitatively evaluated by meta‐analysis. Elevated mean [O3 ] of 116 ppb reduced total biomass of woody plants by 14% compared with control (mean [O3 ] of 21 ppb). Temperate species from China were more sensitive to O3 than those from Europe and North America in terms of photosynthesis and transpiration. Significant reductions in chlorophyll content, chlorophyll fluorescence parameters, and ascorbate peroxidase induced significant injury to photosynthesis and growth (height and diameter). Importantly, subtropical species were significantly less sensitive to O3 than temperate ones, whereas deciduous broadleaf species were significantly more sensitive than evergreen broadleaf and needle‐leaf species. These findings suggest that carbon‐sink strength of Chinese forests is reduced by present and future [O3 ] relative to control (20–40 ppb). Given that (sub)‐tropical evergreen broadleaved species dominate in Chinese forests, estimation of the global carbon‐sink constraints due to [O3 ] should be re‐evaluated. Abstract : Tropospheric ozone is considered the most detrimental air pollutant for vegetation at a global scale, affecting the carbon‐sink capacity of ecosystem and the hydrological cycle. This is the first meta‐analysis including subtropical evergreen broadleaf responses to ozone. Subtropical species were significantly less sensitive to ozone than temperate ones, whereas deciduous broadleaf species were significantly more sensitive to ozone than evergreen broadleaf and needle‐leaf species. The demonstration will greatly improve ozone risk assessment for trees at a global scale, suggesting that estimation of the northern hemisphere carbon‐sink constraints due to ozone should be re‐evaluated.